WOMEN IN TAMIL NADU: TRANSFORMATION TOWARDS LEGAL SECURITY - A STUDY - D., JuliusVijayakumar; A., ClaraJayaKumari (International Journal of Psychosocial Rehabilitation, 2020)
The Christian missionaries were the first to introduce education for women when only one out of a hundred Indian females could read and write in 1834. The role of Carley in abolishing infanticide in India is still remembered in India. Along with Raja Ram Mohan Roy, Carey campaigned against Sati, and finally Lord William Bentinck abolished Sati. After reviewing the Crime Review Reports of Tamil Nadu Police, this study also endorsed the view of Krishnaji, Rustagi, and Mukherjee that most of the crimes against women go underreported for comprehensible motives such as social stigma, disbelief in legal mechanisms, fear of vengeance, and so on.